Peculiarities of trajectory of both general mass centre and body joints mass centres in walking structure of 6–8 year-old children - Kholodov, Serhii (Journal of Education, Health and Sport, 2017)
Topicality. Mechanisms of motor function regulation, as well as matter and its carrier, have a multilevel hierarchical structure of their organization. The simplified structure of motor function at the level of the organism can be represented in the form of structural blocks: an execution unit, including musculoskeletal system; a control unit, the central part of which is the nervous system; blocks of service systems include practically all other systems of an organism among which endocrine, cardiovascular, digestive, respiratory, excretory, etc. should be allocated. The task of the study is to determine the trajectories of the general mass centre and body joints mass centres in the walking structure of 6–8 year-old children. Research methods include analysis of scientific and methodical resources as well as documentary materials, video-metrics, BioVideo application package, methods of mathematical statistics. Research results. The human body, unlike other living organisms, is formed in the process of ontogenesis in such a way that all its mass in the longitudinal direction is parallel to the vector of gravity. The processes of gravitational energy accumulation by the body of observed groups of children objectively reflect such an indicator in the geometry of their masses as the height of the location above the support of the general centre of their bodies mass. Conclusion. In studying the spatial characteristics of walking by 6–8 year-old students, attention was paid to the trajectories of the general mass centre, the centres of the students’ hip, knee and ankle joints.